Quantitative and Qualitative Changes in the Skeletal Muscle Acetylcholinesterase Activity of Oreochromis niloticus Exposed to Methylparathion - Catap, Elena; Pocsidio, Glorina (Science Diliman: A Journal of Pure and Applied Sciences, 2007)
Spectrophotometric assays and histochemical tests for acetylcholinesterase activity in the epaxial skeletal muscle of maturing Oreochromis niloticus after in-vivo exposure to 0.10 mg/L methylparathion showed significant inhibition of the enzyme by the pesticide. The assays manifested enzyme inhibition, after 48 and 96 hours of exposure, of 43.19% and 56.62%, respectively. These results were confirmed by the occurrences of decreased sites of acetylcholinesterase activity in the muscle fibers as exhibited upon performance of histochemical tests.